2021
DOI: 10.1371/journal.pone.0245042
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes are associated with genomic instability in luminal breast cancers

Abstract: Breast cancer is the leading cause of cancer related death among women. Breast cancers are generally diagnosed and treated based on clinical and histopathological features, along with subtype classification determined by the Prosigna Breast Cancer Prognostic Gene Signature Assay (also known as PAM50). Currently the copy number alteration (CNA) landscape of the tumour is not considered. We set out to examine the role of genomic instability (GI) in breast cancer survival since CNAs reflect GI and correlate with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Luminal B tumors of breast, that are positive for estrogen receptor but negative for progesterone receptor, have increased genomic instability and demonstrate increased growth rate and tendency to develop resistance to tamoxifen 32 . Similarly, it has been demonstrated that a genomic instability-related score calculated based on copy number alterations can predict prognosis in luminal A breast cancer 33 . It is now becoming quite evident that genomic instability is a promising target in cancer 34,35 .…”
Section: Introductionmentioning
confidence: 96%
“…Luminal B tumors of breast, that are positive for estrogen receptor but negative for progesterone receptor, have increased genomic instability and demonstrate increased growth rate and tendency to develop resistance to tamoxifen 32 . Similarly, it has been demonstrated that a genomic instability-related score calculated based on copy number alterations can predict prognosis in luminal A breast cancer 33 . It is now becoming quite evident that genomic instability is a promising target in cancer 34,35 .…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, gains at 2p25-p11.1/12p13.33-p11.1 and 9p24.3-p13.1 were five and four times, respectively, more common in QNBC than in TNBC. Gains or amplifications in these regions were previously reported in TNBC tumors uncharacterized for AR status and have been associated with tumor progression [29,34,36,52,[56][57][58]. For example, the region 6p21-p23 encompasses approximately half of the genes on chromosome 6 and one-third of all CpG islands on this chromosome [59].…”
Section: Discussionmentioning
confidence: 93%
“…Recently, more and more scholars have been drawn to genomic instability. Genomic instability can not only initiate cancer, augment progression, and influence the overall prognosis of the affected patient, but also the survival of CC patients 3 , 5 , 22 , 23 . Recent studies have shown that epigenetic modifications and DNA damage from endogenous and exogenous sources could affect genomic instability 24 27 .…”
Section: Discussionmentioning
confidence: 99%